A Screen-Printed Nickel Based Resistance Temperature Detector (RTD) on Thin Ceramic Substrate - (:unkn) unknown (IEEE, 2020)
A flexible nickel (Ni) based resistance temperature detector (RTD) was successfully fabricated for monitoring temperature in automobile and aerospace applications. The RTD was developed by screen printing Ni based ink on a flexible ceramic platform. The ability of the RTD to monitor temperatures varying from 25 degrees C to 200 degrees C, in steps of 25 degrees C was investigated. The results of the RTD demonstrated a linear response with resistive changes as high as 47.1% at 200 degrees C, when compared to its base resistance (20.2 k Omega) at 25 degrees C. A temperature coefficient of resistance (TCR) of 0.3%/degrees C, with a correlation coefficient of 0.9994 was calculated for the RTD. The response of the screen printed RTD is analyzed and presented in this paper.
Keywords: ceramic substrate; flexible; nickel; resistive temperature detector (RTD); screen printing; SELECTIVE DETECTION; SENSOR